Transitioning Vocational Education and Training in Africa : A Social Skills Ecosystem Perspective - Simon McGrath; George Openjuru Ladaah; Heila Lotz-Sisitka; Stephanie Allais; Jacques Zeelen; Volker Wedekind; Presha Ramsarup; David Monk; Luke Metelerkamp; Jo-Anna Russon; Bonaventure Kyaligonja; Glen Robbins; et al. (Bristol University Press, 2023)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. The transition to more just and sustainable development requires radical change across a wide range of areas and particularly within the nexus between learning and work. This book takes an expansive view of vocational education and training that goes beyond the narrow focus of much of the current literature and policy debate. Drawing on case studies across rural and urban settings in Uganda and South Africa, the book offers a new way of seeing this issue through an exploration of the multiple ways in which people learn to have better livelihoods. Crucially, it explores learning that takes place informally online, within farmers'groups, and in public and private educational institutions. Offering new insights and ways of thinking about this field, the book draws out clear implications for theory, policy and practice in Africa and beyond.